ChemInform Abstract: An Effective Method for the Synthesis of 3, 5‐Bis(halomethyl)‐1, 4‐oxaselenanes and Their Derivatives. Issue 34 (26th August 2014) - Potapov, V. A.; Musalov, M. V.; Abramova, E. V.; Musalova, M. V.; Rusakov, Yu. Yu.; Amosova, S. V.
Abstract Oxaselenane derivatives are obtained in reactions of diallyl ether with selenium dichloride and dibromide.